ANALISIS STRATEGI KOMUNIKASI POLITIK MAJELIS RAKYAT PAPUA DALAM PELAKSANAAN PROGRAM ASTA CITA DI PAPUA BARAT DAYA BERDASARKAN TEORI HAROLD D. LASSWELL - Henraman Henraman; Alyn Wulandary; Jofier Geofani Titarsole; Siti Nursyamsiah Nabi (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
This study aims to analyze the political communication strategy of the Papua People's Assembly (Majelis Rakyat Papua/MRP) in implementing the ASTA CITA Program using Harold D. Lasswell's communication theory. A qualitative descriptive approach was employed to explore how MRP communicates government policies to indigenous Papuan communities. Data were collected through in-depth interviews, participant observation, and document analysis involving MRP members, local government officials, traditional leaders, religious leaders, women representatives, youth leaders, and community members. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while the findings were interpreted through Lasswell's five communication elements: Who, Says What, In Which Channel, To Whom, and With What Effect. The findings reveal that MRP functions as a credible political communicator by delivering policy messages through public dialogues, customary meetings, interpersonal communication, mass media, and digital platforms. The communication strategy emphasizes culturally sensitive messages that strengthen public understanding of the ASTA CITA Program, enhance policy legitimacy, and encourage community participation. Despite challenges related to geographical conditions and limited communication infrastructure in Papua, the involvement of customary and religious leaders as local communicators significantly improves message acceptance and public trust. The study concludes that the effectiveness of MRP's political communication strategy depends on the integration of communicators, messages, communication channels, target audiences, and communication outcomes within Papua's socio-cultural context. This research contributes to the development of political communication studies by demonstrating the applicability of Lasswell's communication model in analyzing policy communication strategies implemented by representative institutions in multicultural and geographically complex regions.